Towards distributed acceleration of image processing applications using reconfigurable active SSD clusters: a case study of seismic data analysis. (2018) - Sharafeddin, Mageda; Partamian, Hmayag; Awad, Mariette; Saghir, Mazen A.R.; Akkary, Haitham; Artail, Hassan; Hajj, Hazem; Baydoun, Mohammed
In this work, we propose a high performance distributed system that consists of several middleware servers each connected to a number of FPGAs with extended solid state storage that we call reconfigurable active solid state device (RASSD) nodes. A full data communication solution between middleware and RASSD nodes is presented. We use seismic data analysis as a case study to quantify how and by how much RASSD nodes can accelerate computational throughput. Speedup of seismic data prediction time when both GLCM and Haralick features are accelerated is examined. The distributed system achieves 102× speedup compared to 4-thread openMP implementation and 265× speedup compared to single thread modern CPU performance. Performance is 5× better than previous work reporting speedup on GLCM and Haralick feature analysis when data is local to the FPGA and 20× better than an identical CUDA implementation using modern GPU.